EVALUASI PENYELENGGARAAN PROGRAM PENDIDIKAN KECAKAPAN HIDUP DALAM BIDANG PENDIDIKAN LUAR SEKOLAH - Hasbi, Muhammad (JIV-Jurnal Ilmiah Visi, 2006)
The study is aimed at describing the implementation of Life Skills Education Program, especially related to: (1) the level of the society’s need and the environment support to the program; (2) the characteristic of the learners, facilators’, organizers, learning program, learning materials, and the availability of the facilities; (3) the implementation of the program, especially related to the activities of die learners, facilitators’ and organizers; (4) the program output, especially related to: the life skills gained by the learners and the benefits of the program for the organizers and Community Learning Centres (CLC). The result of descriptive analysis showed the following facts. : First, the level of society’s need for Life Skills Education Program was fairly high. Second, the environment support to the program was fairly sufficient. Third, the characteristics of learners fulfilled the criteria, while the facilitator’s understanding of life skills concept was low and the ratio of facilitators and learner was not sufficient. Moreover, organizers understanding of life skills concept was low, and there were organizers who did not have a clear organization scheme and the delivery of responsibility. Fourth, the learning program was not integrative organized; Fifth, the quality and quantity of primary arid secondary learning material were poor. Sixth, individual learning activities as well as the cross-sector coordination are still poor. Seventh, the supervision of the program implementation was low. Eighth, the learning assessments did not use various techniques, not documented and analyzed well. Ninth, the learner’s achievement of social and vocational skills was fairly good, while their achievement of personal and daily living skills was poor. However, to some extent, the Life Skills Education Program has given benefits to the organizers and Regional RTIU of CLC in South Sulawesi Province Key words: life skills, nonformal education, PBKH program, learning center